Delimitation of genetic conservation units for Dysopsis hirsuta (Müll. Arg.) Skottsb. (Euphorbiaceae), an herb endemic to Juan Fernández Archipelago, Chile - Glenda Fuentes; Hellen Montoya; Patricio López-Sepúlveda; Diego Alarcón; Patricio Peñailillo (Gayana: Botanica)
Juan Fernández Archipelago is made up of islands: Robinson Crusoe, Santa Clara and Alejandro Selkirk and it has high endemism in its small area, and it was declared as Chilean national park, a biosphere reserve and a global biodiversity hotspot. The past introduction of invasive plant and animal exogenous species together with the human activities resulted in species loss and populations damage, affecting the genetic diversity within its endemic species. The aim of this study was to mark out genetic conservation units, also known as ESUs, for the endemic herb Dysopsis hirsuta, within its whole distribution range in Robinson Crusoe Island. Genetic diversity and structure parameters were obtained from AFLP and SNPS molecular markers from samples collected from 321 plants, making genotyping 113 individuals from 9 localities. Results led to marking out three genetic conservation units with populations in Mirador Selkirk-Plazoleta El Yunque, Salsipuedes and Rebaje la Piña, Vaquería y Puerto Inglés. The selection of these units may help in making better conservation strategies, since it separates the genetic singularities shared by populations within each unit. Additional conservation efforts in these three units are encouraged, using tools as seed banking, considering these units in conservation management plans including also La Campana locality, in order to increase the genetic variation levels and to carry out special monitoring to Salsipuedes population due to its singular genetic patterns revealed in the study.